Credit- and permit-based travel demand management state-of-the-art methodological advances. Issue 1 (4th March 2022) - Lessan, Javad; Fu, Liping
ABSTRACT: The idea of roadway transportation as a shared economy and next-generation of mobility services is increasingly becoming a reality with the premise that the roadway system is a collection of scarce commodities, which can be managed by endowing right use to its users. Over the past two decades, a growing body of research has explored different roadway-use right schemes, including credit-and permit-based mobility schemes, with specific focus on the three problems arising in these schemes – pricing, efficient allocation and charging of permits or credits for mobility management. In this paper, we attempt to synthesis the relevant body of literature by presenting an in-depth comprehensive review of the state-of-the-art methodologies for addressing these decision problems. The goal is to provide an improved understanding of the fundamental constructs, problem variants, proposed methodologies, and modelling attributes. We also discuss the research gaps and challenges and suggest some possible perspectives and directions for future research.